2002
DOI: 10.2214/ajr.179.6.1791555
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Positron Emission Tomography—CT: Optimized CT Using Oral and IV Contrast Materials

Abstract: Our whole-body PET-CT protocol provided good vascular and intestinal enhancement without compromising PET quality, leading to a potential improvement in the diagnostic capacity of the combined PET-CT examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(45 citation statements)
references
References 6 publications
0
43
0
2
Order By: Relevance
“…15 Region of interest V is the mean attenuation of the vessel, region of interest M is the mean attenuation of the muscle, and n is noise.…”
Section: Ct Data Analysismentioning
confidence: 99%
“…15 Region of interest V is the mean attenuation of the vessel, region of interest M is the mean attenuation of the muscle, and n is noise.…”
Section: Ct Data Analysismentioning
confidence: 99%
“…Previous studies have shown that scaling errors, although small (mean maximum standardised surface uptake value difference 5-7%), can occur in areas with high iodine concentration (e.g. liver, spleen and aorta) on CT acquisition [19]. As a result of the CT-based attenuation correction when scaling algorithms are used, the resulting overestimation may occur and may lead to image artefacts in the emission data.…”
Section: High-density Attenuation Artefactsmentioning
confidence: 99%
“…contrast agents have advantages in improving the delineation of anatomic structures, the sensitivity in detecting pathologic lesions, and accuracy in lesion characterization, their routine use is controversial because of potential artifacts during CT-based attenuation correction. Highly concentrated focal radiodense contrast may result in an overestimation of FDG uptake in combined PET/CT [10][11][12][13][14][15]. However, when CT images of combined PET/CT are used for diagnostic purposes, those without i.v.…”
mentioning
confidence: 99%